Strawberry Accessions with Reduced Drosophila suzukii Emergence From Fruits - Gong, Xiaoyun; Bräcker, Lasse; Bölke, Nadine; Plata, Camila; Zeitlmayr, Sarah; Metzler, Dirk; Olbricht, Klaus; Gompel, Nicolas; Parniske, Martin (Frontiers in Plant Science, 2016)
Drosophila suzukii is threatening soft fruit production worldwide due to the females’ ability to pierce through the intact skin of ripe fruits and lay eggs inside. Larval consumption and the associated microbial infection cause rapid fruit degradation, thus drastic yield and economic loss. Cultivars that limit the proliferation of flies may be ideal to counter this pest; however they have not yet been developed or identified. To search for potential breeding material, we investigated the rate of adult D. suzukii emergence from individual fruits (fly emergence) of 107 accessions of Fragaria species that had been exposed to egg-laying D. suzukii females. We found significant variation in fly emergence across accessions, which correlated with the genetic make-up of the accessions and fruit diameter, and to a lesser extent with the strawberry species background. We identified accessions with significant resistance to fly emergence, not related to their fruit diameter. These accessions constitute valuable breeding material for strawberry cultivars that limit D. suzukii spread.